Hubungan Ganguan Akibat Kekurangan Yodium (GAKY) dengan Prestasi Belajar di SDN Tanggalrejo Kecamatan Mojoagung Kabupaten Jombang - Pitaloka, Diah Ayu; Ratnawati, Mamik; Ulfa, Ida Nikmatul (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2017)
The Correlation OfÂ Iodine Deficiency DisorderÂ (IDD) WithÂ Learning AchievementÂ At Public Ementary School ( SdnÂ ) Tanggalrejo Village ,Â MojoagungÂ Sud District , In Jombang District. One nutritional problem In indonesia is IDD.Â IDD is known toÂ be able to effectÂ abnormality such as mumps, cretin, intelligence disorder,Â mental disorderÂ and physical development disorder that affectÂ the quality of HR (Human Resources). Impaired intelegence of child, make the child will have difficulty to achieveÂ learning. The research aimedÂ to understandÂ the correlation of IDD withÂ learningÂ achievementÂ atÂ ( SDN )Â TanggalrejoÂ Village, Mojoagung Sub district inÂ Jombang District. This researchÂ wasÂ an analytic correlation with cross sectional approach. TheÂ population as much as 54 respondent wasÂ theÂ Â students ofÂ Â grade 3Â at Public Elementary school ( SDNÂ ) TanggalrejoÂ Village Mojoagung sub district inÂ JombangÂ District , and total ofÂ samples wasÂ Â 54 respondentsÂ with theÂ technique of samplingÂ usedÂ total sampling. The independent variableÂ wasÂ IodineÂ deficiencyÂ Disorders(IDD) and the dependent variableÂ was learning achievement with the instrument in the form of inspection and palpation ofÂ thyroid gland and documentation of the valueÂ withÂ Â Spearman rank test. The results showed that the mostÂ (70.4%) IDD wasÂ 0 degreesÂ and the mostÂ (33.3%) learning achievement was less , itÂ was obtainedÂ r valueÂ = 0.351, Ï = 0.009 and É‘ = 0.05, because Ï <É‘ then HoÂ wasÂ refusedÂ it meantÂ thereÂ wasÂ correlationÂ of IDD with grade 3Â student â€˜s achievementÂ atÂ Â Â Public Elementary SchoolÂ (SDN ) TanggalrejoÂ Village , Mojoagung Sub district inÂ Jombang District.Based on the description above, so that the increase ofÂ iodized salt consumption is needed byÂ school-age children to prevent the emergence of new problems, and as a correction for peopleÂ withÂ IDD. And necessary counceling about the important iodized salt to community.Â Keywords: IDD, Learning Achievement